La evaluación formativa desde los entornos virtuales de aprendizaje (2022)
Evaluation is a process that day by day regains strength in the educational system, seeking a quality in teaching and learning, and must be of a formative nature to be effective. As a result of the COVID-19 pandemic, this study establishes the objective of proposing strategies to accompany teachers at the Virginia Rossi Sister School in Barranquilla (Atlántico) for TIC in formative evaluation. The research is framed in the qualitative approach, the social critical paradigm, the action research type. Twelve ninth-grade students from the Educational Institution and 8 teachers were selected as actors or informants. For the collection of information, the documentary review, the semi-structured interview applied to teachers and the focus group technique for students were used. The results obtained show the confusion between "evaluative test" and "formative evaluation process", the continuity of traditional evaluation strategies and heteroevaluation. A pedagogical proposal for intervention is designed in order to use the didactic support tools offered by TIC to implement strategies and evaluative instruments with formative, permanent, continuous and integral criteria, and thus take into account the development of all dimensions of the person.